(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2019)
An in vitro – in vivo correlation (IVIVC) model can predict the bioavailability of some drug substances, and mitigate against the high cost of bioequivalence studies, long generic product development lead times, and the exposure of human subjects to drug substances they do not need. In this study a total of three batches of generic paracetamol immediate release oral tablets and one batch of the comparator product, were subjected to dissolution testing to generate a dissolution profile from which the blood drug concentration – time profile and specifically the bioavailability parameters AUC and Cmax were computed using an IVIVC tool. Statistical analysis demonstrated sameness between the generic product and the reference product. The IVIVC method can thus be a surrogate for in vivo human studies, providing a scientific justification for biowaiver for generic products of candidate drug substances.